The Influence of International Law in 1945 Constitution Amendments of the Republic of Indonesia - Rudi Natamiharja; Algizca Rasya; Ria Wierma Putri; Desia Rakhma Banjarani (Musamus Law Review, 2022)
As a country that is active in international relations, Indonesia often creates relations about the relationship between international and national law, which also raises questions about the influence between the two. The linkages between international law and national law give rise to each other, including in the process of drafting amendments to the constitution of a country, one of which is Indonesia. This paper discusses the influence of international law in the amendments to the 1945 Constitution of the Republic of Indonesia. The method used is normative juridical in the form of library research. The results of the research are that there is a link between national law and law that influence each other, including in the process of amending the 1945 Constitution of the Republic of Indonesia. Although not all articles are affected by international law, at each stage of the amendment there are several articles that have a positive effect on the whole. directly or indirectly.